Early Childhood Education Teacher’s Readiness of Computer Literacy for Facing The 4.0 Industrial Revolution - Pramudyani, Avanti Vera Risti; Indratno, Toni Kus; Rohmadheny, Prima Suci (Journal of Early Childhood Care and Education, 2019)
Facing the 4.0 Industrial Revolution in education is done by preparing human resources that have critical thinking skills and problem solvers, communication and collaborative skills, creativity and innovative thinking, and literacy of Information and communication technology. This research aims to know the extent of teachers at ECE in the of computer literacy based on their duties and responsibilities as educators in the learning process. This research is using the mixing method (quantitative and qualitative) approach with data collection instruments in the form of questionnaires and interviews. Analysis of the data used is a descriptive analysis deduction, namely analyzing and providing an interpretation of the collected data than needed studies. The subject of this study involved 58 professional certified teachers and had participated in training on ICT topics. The results showed that the level of readiness of teachers in the computer literacy on the readiness of supporting factors is to have a laptop and the basic skills of the applications in the form of MS office (words, PPT, Excel) and search engines only to support they working in organizing the learning administration. The teacher should be mastering of ICT as part of computer literacy including research activities, organizing, evaluating, communicating information, and understanding the rules of use of information and communication technology.